Dark Matter freeze-in during warm inflation and the seesaw mechanism - Rayff de Souza; Jamerson G. Rodrigues; Clarissa Siqueira; Felipe B. M. dos Santos; Jailson Alcaniz (Journal of High Energy Physics)
Abstract A compelling way to address the inflationary period is via the warm inflation scenario, where the interaction of the inflaton field with other degrees of freedom affects its dynamics in such a way that slow-roll inflation is maintained by dissipative effects in a thermal bath. In this context, if a dark matter particle is coupled to the bath due to non-renormalizable interactions, the observed dark matter abundance may be produced during warm inflation via ultra-violet freeze-in. In this work, we propose applying this scenario in the framework of a U(1) B−L gauge extension of the Standard Model of Particle Physics, where we also employ the seesaw mechanism for generating neutrino masses.